House dust mite induced lung inflammation does not alter circulating vitamin D levels - Chen, L.; Perks, K.; Stick, S.; Kicic, Anthony; Larcombe, A.; Zosky, G. (Public Library of Science, 2014)
© 2014 Chen et al. Low circulating levels of 25-hydroxyvitamin D [25(OH)D] are associated with chronic lung diseases such as asthma. However, it is unclear whether vitamin D is involved in disease pathogenesis or is modified by the inflammation associated with the disease process. We hypothesized that allergic inflammation decreases the level of circulating 25(OH)D and tested this using a mice model of house dust mite (HDM) induced allergic airway inflammation. Cellular influx was measured in bronchoalvelar lavage (BAL) fluid, and allergic sensitization and 25(OH)D levels were measured in serum. Exposure to HDM caused a robust inflammatory response in the lung that was enhanced by prior influenza infection. These responses were not associated with any change in circulating levels of 25(OH)D. These data suggest that alterations in circulating 25(OH)D levels induced by Th-2 driven inflammation are unlikely to explain the cross-sectional epidemiological association between vitamin D deficiency and asthma.